Breast Cancer Stigma Scale: A Reliable and Valid Stigma Measure for Patients With Breast Cancer - Bu, Xiaofan; Li, Shuangshuang; Cheng, Andy S. K.; Ng, Peter H. F.; Xu, Xianghua; Xia, Yimin; Liu, Xiangyu (Frontiers in Psychology, 2022)
Purpose: This study aims to develop and validate a stigma scale for Chinese patients with breast cancer. Methods: Patients admitted to the Affiliated Cancer Hospital of Xiangya School of Medicine, Central South University, for breast cancer treatment participated in this study. Development of the Breast Cancer Stigma Scale involved the following procedures: literature review, interview, and applying a theoretical model to generate items; the Breast Cancer Stigma Scale’s content validity was assessed by a Delphi study (n = 15) and patients with breast cancer feedback (n = 10); the principal components analysis with varimax rotation (n = 200) was used to assess the component structure; convergent validity was assessed with the Social Impact Scale (n = 50); internal consistency Cronbach’s α (n = 200), split-half reliability (n = 200), and test-retest reliability (N = 50) were used to identify the reliability of the scale. Results: The final version of the Breast Cancer Stigma Scale consisted of 15 items, and showed positive correlations with the Social Impact Scale (ρ=0.641, P<0.001). Exploratory factor analysis (EFA) revealed four components of the Breast Cancer Stigma Scale: self-image impairment, social isolation, discrimination, and internalized stigma, which were strongly related to our perceived breast cancer stigma model and accounted for 69.443% of the total variance. Cronbach’s α for the total scale was 0.86, and each subscale was 0.75-0.882. The test-retest reliability with intra-class correlation coefficients of the total scale was 0.947 (P<0.001), and split-half reliability with intra-class correlation coefficients of the total scale was 0.911 (P<0.001). The content validity index (CVI) was 0.73-1.0. Conclusions: The newly developed Breast Cancer Stigma Scale offers a valid and reliable instrument for assessing the perceived stigma of patients with breast cancer in clinical and research settings. It may be helpful for stigma prevention in China.